Help! I've been hacked. - DRAKE, CYNTHIA J. (Writer (Madavor Media), 2015)
The article discusses ways freelance writers can protect themselves from data breaches, high-profile hacking and other online attacks. Tips offered include changing passwords frequently and making them hack-proof, using an Employee Identification Number instead of a Social Security Number and keeping anti-virus and anti-malware software up to date. INSET: IT HAPPENED TO ME.